Velocity-based training - A critical review - Guppy, S. N.; Kendall, K. L.; Haff, G. G. (Strength and Conditioning Journal, 2024)
Velocity-based training (VBT) is an increasingly popular programming strategy used by strength and conditioning professionals to develop their athlete's ability to express force rapidly. To implement the varying forms of VBT effectively within their training regimes, strength and conditioning professionals need to understand the strengths and weaknesses of strategies, such as predicting 1 repetition maximum using the load-velocity profile, modulating training loads using the load-velocity profile, and controlling training volume using the magnitude of velocity-loss. The aim of this review was to highlight these strengths and weaknesses and then provide practical examples of when each programming strategy may be most effectively implemented.